2016
DOI: 10.1515/jvetres-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Viral shedders in a herd vaccinated against infection with bovine viral diarrhoea virus (BVDV) without prior testing for the presence of persistently infected animals

Abstract: Introduction: Bovine viral diarrhoea (BVD), caused by the bovine viral diarrhoea virus (BVDV), is one of the most important diseases of cattle worldwide. The purpose of the study was to determine the BVDV infection status in a dairy herd vaccinated against BVD. Before vaccination started in 2008, there had been no prior identification or the removal of the possible source of infection (persistently infected animals). It was expected that vaccination itself would enable the elimination of viral shedders on a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Other studies have shown significant differences in antibody levels in serum from calves receiving modified live virus vaccines based on BVDV-1a, with a significantly lower BVDV-1b antibody titres [35]. PI individuals infected with BVDV-1b were identified in one Polish herd vaccinated with a killed vaccine based on BVDV-1a [36]. Although clinical symptoms resembling BVD were not observed in that herd, the protection offered by vaccinal strain did not provide cross protection against BVDV-1b.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown significant differences in antibody levels in serum from calves receiving modified live virus vaccines based on BVDV-1a, with a significantly lower BVDV-1b antibody titres [35]. PI individuals infected with BVDV-1b were identified in one Polish herd vaccinated with a killed vaccine based on BVDV-1a [36]. Although clinical symptoms resembling BVD were not observed in that herd, the protection offered by vaccinal strain did not provide cross protection against BVDV-1b.…”
Section: Discussionmentioning
confidence: 99%